The Crime of Rape under the Rome Statute of the ICC (with a special emphasis on the jurisprudence of the Ad Hoc Criminal Tribunals) - Nicole Brigitte Maier (Amsterdam Law Forum, 2011)
This article delivers insight into the purposes and intentions of committing rape within wartimes, its victims, its perpetrators, and, finally, under which circumstances the crime of rape is punishable as a crime against humanity. In the first part a definition on crime of rape is given, in this regard relevant literature and case law of both the Yugoslavia Tribunal and the Tribunal of Rwanda will be referred to. On the topics of victims, perpetrators and purposes related literature in the field of psychology, criminology and medical science will be taken into consideration. The discussion on the link between rape and the crime against humanity will focus on relevant cases, judgments and reports, largely of the ICC, the ICTY and the ICTR.